Adopt a Tree - Martha C. Monroe; Christo Frost; Allison W. Bowers (EDIS)
The Forestry Adopt - A - Tree 4-H Project Book (4HFOM11) is for children ages 5-8. Kids locate and "adopt" a nearby tree, track changes to it over time, do bark and leaf rubbings, and search for visiting wildlife. Youngsters are also introduced to three common and special Florida trees: Cabbage Palm, Live Oak, and Longleaf Pine. First published February 2001.